Kulturella perspektiv på högutbildades mobilitet - Öhlander, Magnus; Wolanik Boström, Katarzyna; Pettersson, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2016)
This special issue is based on a panel at the 33rd Ethnology and Folklore Conference in Copenhagen in 2015, and focuses on cultural perspective on international mobility of highly educated employees. The articles’ joint analytical input can be summarized in Russell King’s (2002) phrase “double embeddedness of migration”. Everyday life and people’s narrated experiences are at the heart of the articles, but the focus is also set on the intersection of structural conditions and individual life circumstances. Mobility across national borders contributes with new experiences and knowledge and has different kinds of impact on social status and the individual’s resources acquired by education. This is something the voluntarily mobile have in common with those who are forced to leave their countries of origin. However, there are crucial differences in how highly skilled professionals are received and regarded in the countries they come to, the status they can achieve and the framework within which they can make use of their assets.